A new species and new record of the genus Discoelius Latreille, 1809 (Hymenoptera: Vespidae: Eumeninae) from China - Wang, Hua-Chuan; Chen, Bin; Li, Ting-Jing (Zootaxa, 2019)
Discoelius brevilamellatus Wang, Chen & Li, sp. nov. is described and illustrated from Tibet, China, and Discoelius turneri (Meade-Waldo, 1910) is newly recorded from China.